THE CONDITION AND DISTRIBUTION OF STONY CORALS (Scleractinia corals) IN BANGKA WATER - Rikoh Manogar Siringoringo; Tri Aryono Hadi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Bangka water is well known as the best tin producer in which there are many off-shore tin-mining activities conducted by both local people and tin companies. Such condition apparently brings negative impacts to marine life. Stony corals are considered as the major component of coral reef ecosystems whose condition is influenced by environmental condition. The aim of this study is to observe the general condition of coral reefs and the distribution of stony corals in Bangka Water. The study was carried out between September and November 2010 by taking 10 stations. The method used was LIT as long as 70 meters installed parallel to the coast line. The result indicates that generally the condition of coral reef was categorized as fair condition, the coral cover averaging at 47, 82 %. There were 89 species of stony corals found, divided into 13 genera. The most dominant species was Porites lutea , particularly at Station 6 by 33,3%. The prolonged turbidity mainly caused by tin-mining activities is thought to lead the coral reefs to critical condition particularly in some areas. Keywords: stony corals, coral cover, distribution, Bangka Water.